Histopathological Effects of Pesticide Imidacloprid Insecticide on the Liver in Male Rabbits - Al-Arami, Ateeq M.J; AL-Sanabani, Abdulwahab S.M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Excessive use of pesticides has led to increasing concern about undesirable effects on human health and the environment. Imidacloprid is an internationally used neonicotinoid insecticide due to its significant toxicity to insects. Its residues may reach the food chain, which is important for examining the potentially harmful properties of imidacloprid exposure. The current study aimed to characterize the histopathological effects of imidacloprid on the liver of male rabbits. The Imidacloprid administration daily at the two chronic oral doses of (45 mg/kg and 90 mg/kg, daily) for 37 days. Treated male rabbits groups for treatment concentrations revealed many histopathological changes in the liver, such as congestion of blood vessels, hemorrhage, inflammation, ballooned hepatocytes, steatosis, infiltration, vasodilatation, necrosis and fibrosis. The study results established that Imidacloprid was significantly worse in specific organs in the digestive system (liver) of male rabbits.